Volume 2: Combustion, Fuels and Emissions, Parts a and B 2010
DOI: 10.1115/gt2010-22478
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Engineering Gas Turbine Emission Performance: Applied to an Aircraft Auxiliary Power Unit

Abstract: Environmental and future supply pressures are expected to drive aviation towards alternative fuel sources. However little is available in the literature on aircraft landing-takeoff (LTO) cycle gaseous emissions resulting from the combustion of alternative fuels. Considering the different engine configurations existing in today’s commercial aviation fleet, emission experiments of alternative fuels on all engine types are almost impossible. Modelling may provide a solution but the availability of combustor data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…calculated and measured emissions data in this respect. A Genetic Algorithm approach [4,5] was selected as the most suitable method for this purpose because it is easy to implement without the need to rearrange the governing equations. This is a self-contained solution for problems of a black box process rather than a competition with methods using CFD.…”
Section: Methodology Of the Chemical Reactors Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…calculated and measured emissions data in this respect. A Genetic Algorithm approach [4,5] was selected as the most suitable method for this purpose because it is easy to implement without the need to rearrange the governing equations. This is a self-contained solution for problems of a black box process rather than a competition with methods using CFD.…”
Section: Methodology Of the Chemical Reactors Networkmentioning
confidence: 99%
“…The fuel injector design is a slinger system which injects the fuel into the primary combustion zone through a row or two rows of holes from the shaft by taking advantage of centrifugal forces acting on the fuel spray by rotating the shaft to assist fuel atomisation. The CO, NO x and UHC emissions of Jet fuel (JetA-1), synthetic gas to liquid jet fuel (GTL), JetA-1 and GTL 50/50 by volume blend and rapeseed bio-diesel were collected during the campaign [1,4,20]. The APU was started on Jet A-1 and once stabilised, it was switched over to an alternative fuel.…”
Section: The Auxiliary Power Unit (Apu) Alternative Fuels Emissions Cmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper is intended to show an alternative way to analyse one part of this challenge, hydrogen emissions, by using simulation. The Genetic Algorithms optimised Chemical Reactors Network (GACRN) [2] has shown that it is possible to reverse engineer the combustor flow splits and reactor sizes by matching the experimental data and forward predict alternative fuels emissions in an Auxiliary Power Unit (APU). Therefore it was applied to convey the study of NOx emissions in a LandingTakeoff (LTO) cycle of hydrogen as a drop-in fuel in a V2527 engine and as an alternative fuel in a modified V2527 engine.…”
Section: Introductionmentioning
confidence: 99%